Korelasi tingkat kecemasan saat persalinan dengan lamanya proses kelahiran pada ibu bersalin - Ani; Strahmawati Hamzah; Suhartini; Astri Yuliandini; Abdul Thalib (THE JOURNAL OF Mother and Child Health Concerns, 2025)
Background: The anxiety experienced by the mother when facing the labor process can prolong the duration of labor and risk causing long partus. About 30% of pregnant women experience anxiety before childbirth, which if left untreated can negatively impact the delivery process. Purpose: This study aims to determine the relationship between the level of anxiety of maternal mothers and the incidence of long partus at Daya Hospital. Method: This study used an observational design with a cross-sectional approach. The sample consisted of 30 maternal respondents with long partus who were taken using a saturated sampling technique. Data were collected through the Taylor Manifest Anxiety Scale (T-MAS) questionnaire and the long-term partus incidence questionnaire and analyzed using the Fisher Exact test. Results: As many as 90% of mothers with prolonged partus experienced anxiety, and the majority had mild anxiety levels (60%). The results of the analysis showed a p value 0.041 (< 0.05), which means that there is a significant relationship between maternal anxiety and the incidence of long partus. Suggestion: Consistent psychological intervention and emotional support to pregnant women before and during childbirth is needed to lower anxiety levels and prevent prolonged partus. Support from health workers, families, and antenatal education needs to be increased.